Formation of Aminocyclopentadienes from Silyldihydropyridines: Ring Contractions Driven by Anion Stabilization. Issue 22 (26th April 2018) - Walker, Morgan M.; Chen, Shuming; Mercado, Brandon Q.; Houk, K. N.; Ellman, Jonathan A.
Abstract: Highly functionalized aminocyclopentadienes can be formed through the rearrangement of anions generated from readily prepared 6‐silyl‐1, 2‐dihydropyridines by desilylation with fluoride. The scope and generality of the reaction was defined, and diverse transformations were performed on the highly functionalized products. A mechanism and driving force for the rearrangement were identified from experiments and DFT calculations. Abstract : A new contract(ion) : Densely functionalized aminocyclopentadienes are efficiently accessed through anionic rearrangement of 6‐silyl‐1, 2‐dihydropyridines. DFT calculations were performed to elucidate the mechanism of this transformation.